Academic Social Networks and Open Access: French Researchers at the Crossroads - Okret-Manville, Christine (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
Researchers benefit from an increasing array of tools to enhance direct communication and the dissemination of their research findings. These include Open Access repositories, Open Access journals, or hybrid publishing. For some years, researchers have been using new ways to communicate and share their work by using academic social networks. In an attempt to foster the development of Open Access in France, the French consortium COUPERIN (Unified Consortium of Higher Education and Research Organizations for Access to Numerical Publications) proposed that academic social networks could be used to convince researchers of becoming more involved in Open Access. To test this hypothesis, a nationwide survey was launched in 2014 to explore whether and how these academic social networks are used to share content, but also how they compare to other Open Access classic tools. Within a month (20 May to 20 June), 1,898 researchers answered this 28-question survey. It was fully completed by 1,698 of them. This provides COUPERIN with considerable data for analysis. The respondents roughly reflect the composition of the French academic community in terms of gender and research fields, with a slight overrepresentation of young researchers/ PhD candidates. This survey does not, however, cover the in-depth opinions of researchers on Open Access and academic social networks. It therefore only presents general tendencies. Nonetheless, the survey gives many indications as to how researchers apply Open Access. In addition, it shows how they feel about the usefulness of these networks compared to repositories when efficiently disseminating their work. This survey also takes the differences between disciplines into account and characterizes behaviour and opinions according to the different disciplinary communities and their research practices. Finally, this survey allows us to define the main characteristics of a tool which could meet French researchers’ needs for scientific communication. The components of such an ideal tool dedicated to Open Science could include efficient repositories to easily disseminate work and improve visibility, a sharing network and the scientific stamp of peer-review.